Pneumocystis Colonization in Immunocompetent and Simian Immunodeficiency Virus-infected Cynomolgus Macaques - Kling, Heather M.; Shipley, Timothy W.; Patil, Sangita; Morris, Alison; Norris, Karen A. (The Journal of infectious diseases, 2009)
Pneumocystis (Pc) colonization is common among human immunodeficiency virus (HIV)-infected subjects, although the clinical consequences of Pc carriage are not fully understood. We examined the frequency of asymptomatic carriage in healthy and simian immunodeficiency virus (SIV)-infected cynomolgus macaques by use of polymerase chain reaction (PCR) and assessment of changes in the serologic response to a recombinant fragment of the Pc protein kexin (KEX1). Anti-KEX1 antibodies were detected in 95% of healthy monkeys. To create a model of natural transmission of Pc, SIV-infected monkeys were cohoused with macaques coinfected with SIV and Pc. Pc colonization occurred when the CD4+ T cell count decreased to <500 cells/µL, despite anti-Pc prophylaxis with trimethoprim-sulfamethoxazole. Increases in anti-KEX1 antibody titers preceded detection of Pc DNA in bronchoalveolar lavage (BAL) fluid samples by use of PCR. These results demonstrate the usefulness of recombinant KEX1 in serologic studies of Pc colonization and will improve the understanding of Pc transmission and clinical consequences of Pc colonization in HIV-infected patients.